Application Strategies of Super-Enhancer RNA in Cardiovascular Diseases - Yi He; Yuwei Cai; Yanyan Cao; Yan Wang; Jing Wang; Hu Ding (Biomedicines)
Cardiovascular diseases (CVDs) are a leading cause of death worldwide, and new therapeutic strategies are urgently needed. In recent years, enhancer RNAs (eRNAs) have gradually attracted attention because they offer new directions for the treatment of CVDs. Super-enhancer RNAs (seRNAs) are a subset of non-coding RNAs that are transcribed from regions of the genome known as super enhancers, which are large clusters of enhancers with a high density of transcription factors and cofactors. These regions play a pivotal role in regulating genes involved in cell identity and disease progression. This article reviews the characteristics of seRNAs, their expression patterns, and regulatory mechanisms in the cardiovascular system. We also explore their role in the occurrence and development of CVDs, as well as their potential as diagnostic biomarkers and therapeutic targets. Currently, therapies targeting seRNAs are a research hotspot. The development of specific inhibitors or activators is expected to facilitate precise interventions for CVDs. In addition, the use of gene editing techniques to modify relevant eRNA introduces new possibilities for disease treatment. This review aims to provide a comprehensive overview of seRNAs in CVDs and discusses their potential as a novel class of therapeutic targets.